Luigi Ghirri Italian Memories. Landscape and Architecture - Maglione, Biancalucia (Revelar: Revista de Estudos da Fotografia e Imagem, 2016)
«I did not tried to produce PHOTOGRAPHS, but rather CHARTS or MAPS that were photographs at the same time» (Ghirri, L.,1979: 63-64). Since the late 1960s, Luigi Ghirri received attention as landscape photographer with an original and attentive perspective. Ghirri's pictures precisely outline a map of the Italian human, natural and architectural landscape. In the '8os, in fact, the architect and friend Vittorio Savi "discovered" Ghirri as architectural photographer, convincing him to "portray" the works of great Italian architects, starting from the cemetery of San Cataldo in Modena by Aldo Rossi, whose photos were then published on the Architectural Magazine 'Lotus International'. This was the first example of a renewed photograph-architecture relationship, where the first is not just a "documentation" of the second, but also a work with its own artistic autonomy. The purpose of my paper is to investigate the way in which Ghirri's pictures, especially those portraying the works of urban planners, provide a new iconography of the Italian landscape, defining a clear identity, and creating "areas of memory", as Ghirri himself used to say, examples of historical and contemporary objects at the same time, scenes of possible events although not described yet. While taking into account the influence that conceptual art had on Ghirri, I will then analyze a range of case studies, in particular drawn from the large "Paesaggio italiano" (1980-1992), and from 'Viaggio in Italia' (1984) - a journey from Bari to Reggio Emilia, which was supposed to investigate the changes in the Italian landscape between the '6os and '7os. In this way, it is possible to explore the role of photography in Ghirri in portraying and understanding the country's genius loci and inlaying the foundations for shaping a recognizable aesthetics of the Italian landscape and providing at the same time a critical interpretation of it.